Functionalized polymeric materials in agriculture and the food industry - Akelah, Ahmed (Springer US, 2013)
This book looks at the applications of polymeric materials in agriculture and the food industry as a way to meet the growing demands of food production and to reduce the environmental pollution associated with the use of agrochemicals.   Following a detailed description of polymeric materials, Part I addresses in depth their use in both agriculture and agrochemicals. Part II focuses more closely on the role of polymeric materials in food, more specifically in food processing of especially dairy, sugar, juices and water, food additives, and food packaging and protection.     About the Author Ahmed Akelah is currently Professor Emeritus of Polymer Chemistry at Tanta University, Egypt. He received his Dr. rer. nat. degree from Bonn University, Germany (1978) and his D.Sc. from Cairo University (2010) with a dissertation titled Reactive Functionalized Polymers and Nanocomposites and Their Applications for Achieving Green Chemistry in Chemical Reactions and Agriculture.